Genotype and Phenotype Heterogeneity in Neonatal Diabetes: A Single Centre Experience in Turkey - Yasemin Denkboy Öngen; Erdal Eren; Özgecan Demirbaş; Elif Sobu; Sian Ellard; Elisa De Franco; Ömer Tarım (Galenos Yayincilik, 2021)
Objective:Neonatal diabetes mellitus (NDM) may be transient or permanent, and the majority is caused by genetic mutations. Early diagnosis is essential to select the patients who will respond to oral treatment. In this investigation, we aimed to present the phenotype and genotype of our patients with NDM and share our experience in a single tertiary center.Methods:A total of 16 NDM patients from 12 unrelated families are included in the study. The clinical presentation, age at diagnosis, perinatal and family history, consanguinity, gender, hemoglobin A1c, C-peptide, insulin, insulin autoantibodies, genetic mutations, and response to treatment are retrospectively evaluated.Results:The median age at diagnosis of diabetes was five months (4 days-18 months) although six patients with a confirmed genetic diagnosis were diagnosed >6 months. Three patients had KCNJ11 mutations, six had ABCC8 mutations, three had EIF2AK3 mutations, and one had a de novo INS mutation. All the permanent NDM patients with KCNJ11 and ABCC8 mutations were started on sulfonylurea treatment resulting in a significant increase in C-peptide level, better glycemic control, and discontinuation of insulin.Conclusion:Although NDM is defined as diabetes diagnosed during the first six months of life, and a diagnosis of type 1 diabetes is more common between the ages of 6 and 24 months, in rare cases NDM may present as late as 12 or even 24 months of age. Molecular diagnosis in NDM is important for planning treatment and predicting prognosis. Therefore, genetic testing is essential in these patients.